Improving Peat Engineering Properties by Natural Mineral Mixture - Nurmunira, Muhammad; Abdoullah, Namdar; Ideris, Zakaria (Penerbit UMP, 2012)
The mixed soil is appropriate technique for solve geotechnical engineering problems. The main problem of case study is spreading peat in vast area. The exaction and replacing soil from far distance resulted in finishing project with high cost. In this regard improving peat mechanical properties by using modified kaolin under, 200°C, 400°C, 600°C and 800°C heat has been investigated. The liquid limit, plastic limit and dry density are main objectives in this research work. The result indicated that the new minerals are developed during modifying kaolin submitted to heat and it is improving peat liquid limit and plastic limit. And in soil mixture dry density is reduced, it is expected to improve peaty subsoil allowable deformation by using this technique in site. Thus further investigations are needed for assessing specimen shear strength, bearing capacity, settlement and deformation.